2021
DOI: 10.1007/s10643-021-01232-y
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Commitment of Chinese Kindergarten Teachers During the COVID-19 Pandemic: Predictions of Anti-Epidemic Action, Income Reduction, and Career Confidence

Abstract: This study highlights a survey on 5783 kindergarten teachers’ occupational commitment and its influencing factors in the socioeconomic context of China during the COVID-19 pandemic. Data were collected through the WenJuanXing public online platform. Quantitative analysis results showed that kindergarten teachers’ occupational commitment was optimistic on the whole during this period, among which the affective commitment and the normative commitment were satisfactory, but the continuing commitment needed to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 65 publications
(70 reference statements)
2
16
0
Order By: Relevance
“…Some teachers were reported to have retired early in order to avoid face-to-face teaching during the pandemic. Wei et al (2021) suggest a reduction in the commitment levels of teachers due to the measures taken on teachers, such as salary reduction and changes in the work environment. Each demographic group showed a reduction in the commitment levels of teachers with a different pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Some teachers were reported to have retired early in order to avoid face-to-face teaching during the pandemic. Wei et al (2021) suggest a reduction in the commitment levels of teachers due to the measures taken on teachers, such as salary reduction and changes in the work environment. Each demographic group showed a reduction in the commitment levels of teachers with a different pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Much more, that it was made feasible by ECPs' efforts and the investment of available resources. In this vein, interviewees commonly displayed high occupational commitment during the reopening phase which accords to international literature with Chinese kindergarten teachers during COVID-19 [78]. From an infection prevention led perspective, it matters which measures are accomplished and how, but from an occupational health psychology perspective, what the consequences are for staff, too.…”
Section: Practical Implementation Of Preventive Measures and Associat...mentioning
confidence: 99%
“…The fear of the virus and the restrictions imposed due to its outbreak had a tremendous effect on mental health and changed many facets of people’s lives including at work. According to studies, the well-being and engagement of workers in general, and teachers in particular, has been affected [ 2 , 3 ]. Even before the pandemic, teaching identified as a profession that is prone to stress and burnout due to the heavy workload [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two longitudinal studies comparing mental health indicators before and during the pandemic found that during the pandemic, teachers’ anxiety levels were high and that their quality of life and optimism had decreased [ 2 , 15 ]. The difficulties that teachers continue to encounter during the pandemic crisis have affected their work engagement as well [ 3 , 16 ]. Work engagement is an affective-motivational construct defined as a positive, fulfilling, work-related state of mind characterized by high levels of energy while working, strong involvement in one’s work, and concentration and engrossment in work [ 17 ].…”
Section: Introductionmentioning
confidence: 99%